Examining the influence of user-generated content on the fashion consumer online experience. Issue 3 (22nd December 2020) - Vazquez, Delia; Cheung, Jenny; Nguyen, Bang; Dennis, Charles; Kent, Anthony
Abstract : Purpose: The purpose of this study is to analyse online consumers' experiential responses towards visual user-generated content in social commerce fashion online shopping environments. The study develops and tests a UGC OCE framework incorporating aesthetic and relational experiential paths in the OCE. Design/methodology/approach: This paper adopts a quantitative approach to examine fashion consumers experiential responses to UGC content. The sample comprised 555 respondents recruited via a consumer panel. SEM analysis was employed to analyse and test the framework model. Findings: The findings illustrate that consumers are initially stimulated by an aesthetic experience, which then triggers a combination of relational, emotional and interactive experiences in fashion social commerce. The study extends the S-O-R framework by integrating it to the experiential "path" that indicates the series of experiences consumers encounter. Using S-O-R, the study presents the consumers' online experiential responses to viewing visual UGC, revealing that there are five experiential responses, all of which have an influence on online consumer behaviour. Responses towards visual UGC include visual, relational, emotional, cognitive engagement and interactive engagement, which were all identified to influence purchase intention. Originality/value: This study is original in finding that, in the context of online fashion shopping, aesthetics drive relational experiences, and relational experiences drive flow and interactive behaviour and also purchase intention. Aesthetic experiences and positive emotions are powerful drivers of purchase intention and drive connectedness, flow and interactive behaviour. This study extends the literature by extending the frameworks in OCE and CE into the fashion UGC context.